SPARE PARTS SALES APPLICATION IN STORES MSCOM COMPUTER USING VISUAL BASIC 6.0 - Ahmad Ihsan (Jurnal Sistem Informasi, 2007)
In writing this scholarly authors describe the design of application programs of data processing computer spare part sales at stores MSCOM particularly in the sale of goods transactions in cash and cash purchases by using Microsoft Visual Basic 6.0 and Visual Data Manager (VisData) to create a database.